2005
DOI: 10.1007/s00415-005-0641-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of elderly patients with a cautious gait of unknown origin

Abstract: Older adults with a disturbed gait of unknown origin appear to share common characteristics. They walk more slowly than "healthy" controls with increased unsteadiness and with excessive fear of falling. The extrapyramidal, frontal lobe, and limbic systems apparently play an important role, to different degrees, in what can be viewed as a multisystem neurodegenerative syndrome clearly different from "aging."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 40 publications
5
91
0
3
Order By: Relevance
“…This implies that "cautious gait" is caused by an underlying pathology and/or by decreased physical activity. This notion is supported by Giladi et al (2005) and Bloem et al Table 3 Regression equation variables (mean (standard deviation) and median) that represent the linear relationship between step length (cm) and step frequency (steps/min) for walking at diVerent speeds, classiWed into four diVerent age groups a intercept, b regression coeYcient, R correlation coeYcient, R2 coeYcient of determination * SigniWcant diVerence of P < 0.050 64-69 year olds (n = 10) 70-74 year olds (n = 10) 75-79 year olds (n = 10) 80-85 year olds (n = 10) (2000) who identiWed possible disease-related causes for the adoption of a "cautious gait" pattern in groups of older patients with "senile gait" disorder. Based on their results, Giladi et al and Bloem et al claim that it is likely that the gait changes in older adults who walk with a "cautious gait" pattern, are a marker of underlying pathology and not a consequence of age-related processes.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This implies that "cautious gait" is caused by an underlying pathology and/or by decreased physical activity. This notion is supported by Giladi et al (2005) and Bloem et al Table 3 Regression equation variables (mean (standard deviation) and median) that represent the linear relationship between step length (cm) and step frequency (steps/min) for walking at diVerent speeds, classiWed into four diVerent age groups a intercept, b regression coeYcient, R correlation coeYcient, R2 coeYcient of determination * SigniWcant diVerence of P < 0.050 64-69 year olds (n = 10) 70-74 year olds (n = 10) 75-79 year olds (n = 10) 80-85 year olds (n = 10) (2000) who identiWed possible disease-related causes for the adoption of a "cautious gait" pattern in groups of older patients with "senile gait" disorder. Based on their results, Giladi et al and Bloem et al claim that it is likely that the gait changes in older adults who walk with a "cautious gait" pattern, are a marker of underlying pathology and not a consequence of age-related processes.…”
Section: Discussionmentioning
confidence: 82%
“…To separate the eVects of age per se from the eVects of severe agerelated neuromusculoskeletal conditions and/or deconditioning due to a sedentary life style, only physically active community-dwelling older women were included. Since a reduced step length is mentioned as a main characteristic of "cautious gait" (Elble et al 1992;Giladi et al 2005;Nutt et al 1993;Nutt 2001;Sudarsky 2006;Wall et al 1991), the present study focused on age-related changes of the step length-frequency relationship during undisturbed walking at diVerent walking speeds as well as during walking while performing a simultaneous cognitive or upper-extremity motor task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This disorder has been termed a 'higher level gait disturbance' (Nutt, Marsden, & Thompson, 1993) or cautious gait. In a study of 24 older adults (72 to 88 years of age; mean: 78) with a HLGD and age and sex matched controls (n = 28), we found that stride variability was significantly larger (p < .0001) in the participants with HLGD (55.6 ± 29.4 ms) compared to controls (24.1 ± 7.3 ms) (Giladi, Herman, Reider-Groswasser, Gurevich, & Hausdorff, 2005;. Participants with HLGD also more frequently showed extrapyramidal and frontal release signs compared to controls, but there was no difference in cerebellar or pyramidal function.…”
Section: Falls In Older Adults With Higher Level Gait Disturbance (Hlgd)mentioning
confidence: 84%
“…Past studies differentiate between gait strategies by evaluating temporal-spatial parameters, such as speed, step length, stance time and step width [22][23][24][25][26]. For instance, in an effort to improve anterior -posterior balance, adults walk with a slower speed, shorter step length and greater stance time [26,27].…”
Section: Experiments 1: Introductionmentioning
confidence: 99%